Differential Diagnosis in Spine Surgery - Koerner, John D (Jaypee Brothers Medical Publishers, 2010)
Practical guide to diagnosis of spine related disorders covering both adult and paediatric conditions. Each topic includes typical case presentations and intiial work up. Internationally recognised author team.